2012
DOI: 10.1371/journal.pone.0035081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Virus LbFV and of Wolbachia in a Host-Parasitoid Interaction

Abstract: Symbionts are widespread and might have a substantial effect on the outcome of interactions between species, such as in host-parasitoid systems. Here, we studied the effects of symbionts on the outcome of host-parasitoid interactions in a four-partner system, consisting of the parasitoid wasp Leptopilina boulardi, its two hosts Drosophila melanogaster and D. simulans, the wasp virus LbFV, and the endosymbiotic bacterium Wolbachia. The virus is known to manipulate the superparasitism behavior of the parasitoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…Lack of a significant effect of wMel on the interaction of Lb with D. melanogaster (two backgrounds) was also reported by Martinez et al (2012). Other strains of Wolbachia are reported to have negative and positive effects on the interaction of D. simulans with Lb (Fytrou et al, 2006;Martinez et al, 2012), but these effects are dependent on whether or not Lb carries the virus LbFV (Martinez et al, 2012), which does not occur in the Lb strain used in our study (Gueguen et al, 2011). Thus, it appears that in D. melanogaster, at least, Wolbachia wMel does not significantly influence the outcome of oviposition by Lb.…”
Section: Discussionsupporting
confidence: 57%
“…Lack of a significant effect of wMel on the interaction of Lb with D. melanogaster (two backgrounds) was also reported by Martinez et al (2012). Other strains of Wolbachia are reported to have negative and positive effects on the interaction of D. simulans with Lb (Fytrou et al, 2006;Martinez et al, 2012), but these effects are dependent on whether or not Lb carries the virus LbFV (Martinez et al, 2012), which does not occur in the Lb strain used in our study (Gueguen et al, 2011). Thus, it appears that in D. melanogaster, at least, Wolbachia wMel does not significantly influence the outcome of oviposition by Lb.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, the presence of Wolbachia in D. simulans did not always improve the flies' resistance to the fungal pathogen Beauveria bassiana (Fytrou et al, 2006), diverse viruses (Martinez et al, 2014;Osborne et al, 2009) or bacteria (Wong et al, 2011). Furthermore, although Martinez et al (2012) found no effect of wRi in flies parasitized by the parasitoid wasp Leptopilina boulardi, Fytrou et al (2006) showed that the same endosymbiotic bacterial strain increased the susceptibility of the flies to the closely related parasitoid wasp L. heterotoma. Thus, the role of Wolbachia in the susceptibility to other parasites appears extremely variable between host-Wolbachia-parasite systems, and may depend on the Wolbachia strain and the host genotype or species (Bordenstein et al, 2003;Hornett et al, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…These studies are mostly laboratory based, with just a few using natural host populations (Skelton et al, 2016;Zele et al, 2014), and only some with parasitoids rather than pathogen infection (Fytrou et al, 2006;Hsiao, 1996;Martinez et al, 2012;Xie et al, 2014). In order to understand the complex role of endosymbionts, such studies should also be conducted under natural conditions, and in a broad range of host taxa.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, females have similar lifetime expectancy, although they incur a modest cost on size (Varaldi et al 2005). Interestingly, the virus also brings a slight protection for the wasp egg against the immune reaction of some Drosophila strains (Martinez et al 2012), underlying the multidimensionalty of the relationship between the virus and the wasp.…”
Section: Introductionmentioning
confidence: 99%